On the morphosyntax and pragmatics of -in in Colloquial Jakartan Indonesian. Issue 130 (1st September 2016) - Arka, I Wayan; Yannuar, Nurenzia
ABSTRACT: This paper presents a novel description and analysis of the suffix -in in colloquial Jakartan Indonesian (CJI), providing the first explicit account of the syntax-semantics-pragmatics interface of this suffix in Indonesian. It demonstrates that - in has its own place in Indonesian grammar, in which certain morphosyntactic functions overlap with its -i/-kan counterparts in Standard Indonesian. Like -i/-kan, -in is a polysemous suffix; its applicative and causative functions are the product of a complex process involving predicate composition of the root and suffix during affixation. This analysis addresses not only clear cases of functional correspondence between the suffixes, but also the deeper morphosyntactic, semantic and pragmatic constraints responsible for certain intriguing differences between -in and -i/-kan .